The Influence of the Extemporaneous Method on Junior High School Students Arabic Speaking Skills - Berliyans Larasati; Miatin Rachmawati (Jurnal Studi Guru dan Pembelajaran, 2024)
Arabic learning is a process in which students learn Arabic with the help of a teacher. In this process, various components are arranged with the main aim of achieving mastery of Arabic knowledge and skills, including comprehension of Arabic material, making sentences in Arabic and the like. The importance of mastering Arabic language skills is one of them, namely speaking skills. In this study proposed the extemporan method as an approach in Arabic speaking skills. This study used a quantitative approach with experimental research techniques using pre-experiment with a one group pretest-posttest design model. The analytical techniques used in this study are Normality Test, Homogeneity Test, Correlation Coefficient, and T Test (Partial) with a sigification level of 5%. The sample used in this study was grade VIII students of SMP Muhammadiyah 2 Kota Tangerang. The results showed that the extemporan method had a significant effect on improving the Arabic speaking skills of grade VIII students of SMP Muhammadiyah 2 Tangerang City with a significance value (p-value) of < 0.05. Based on the results of the study, it can be concluded that the extemporan method is effective in improving the Arabic speaking skills of grade VIII students of SMP Muhammadiyah 2 Tangerang City.